An Enumerative Review and a Meta‐Analysis of Primed Goal Effects on Organizational Behavior. Issue 1 (6th February 2020) - Chen, Xiao; Latham, Gary P.; Piccolo, Ronald F.; Itzchakov, Guy
Abstract : Drawing on results from 32 published and 20 unpublished laboratory and field experiments, we conducted an enumerative review of the primed goal effects on outcomes of organizational relevance including performance and the need for achievement. The enumerative review suggests that goal setting theory is as applicable for subconscious goals as it is for consciously set goals. A meta‐analysis of 23 studies revealed that priming an achievement goal, relative to a no‐prime control condition, significantly improves task/job performance ( d = 0.44, k = 34) and the need for achievement ( d = 0.69, k = 6). Three moderators of the primed goal effects on the observed outcomes were identified: (1) context‐specific vs. a general prime, (2) prime modality (i.e., visual vs. linguistic), and (3) experimental setting (i.e., field vs. laboratory). Significantly stronger primed goal effects were obtained for context‐specific primes, visual stimuli, and field experiments. Theoretical and managerial implications of and future directions for goal priming are discussed.